Polybenzimidazoles tethered with N-Phenyl 1,2,4-triazole units as polymer electrolytes for fuel cells - Potrekar, R. A.; Kulkarni, M. P.; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
Polybenzimidazole (PBI) polymers tethered with N-phenyl 1,2,4-triazole (NPT) groups were prepared from a newly synthesized aromatic diacid, 3'-(4-phenyl-4H-1,2,4-triazole-3,5-diyl) dibenzoic acid (PTDBA). The obtained polymers show superior thermal and chemical stability and good solubility in many aprotic solvents. The inherent viscosities of all polymers were around 1 dL/g. They exhibit high thermal stability with initial decomposition temperature ranging from 515 to 530 degrees C, high glass transition temperature ranging from 375 to 410 degrees C, and good mechanical properties with tensile stress in the range of 66-98 MPa and modulus 1897-2600 MPa. XRD analysis indicates that these polymers are amorphous in nature. PhysicochemiCal properties such as water and phosphoric acid-uptake, oxidative stability, and proton conductivity of membranes of these polymers have also been determined. The proton conductivity ranged from 4.7 x 10(-3) to 1.8 x 10(-2) S cm(-1) at 175 degrees C in dry conditions. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2289-2303, 2009
Keywords: fuel cells; Polybenzimidazole; synthesis and characterization; Triazole